2012
DOI: 10.1124/jpet.112.191528
|View full text |Cite
|
Sign up to set email alerts
|

The β2-Adrenoceptor Agonist Formoterol Stimulates Mitochondrial Biogenesis

Abstract: Mitochondrial dysfunction is a common mediator of disease and organ injury. Although recent studies show that inducing mitochondrial biogenesis (MB) stimulates cell repair and regeneration, only a limited number of chemicals are known to induce MB. To examine the impact of the ␤-adrenoceptor (␤-AR) signaling pathway on MB, primary renal proximal tubule cells (RPTC) and adult feline cardiomyocytes were exposed for 24 h to multiple ␤-AR agonists: isoproter-, and formoterol (selective ␤ 2 -AR agonist). The Seahor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 42 publications
2
79
1
3
Order By: Relevance
“…RPTCs were plated in XF-96 plates and grown under improved culture conditions that maintain polarity, differentiated function, and respiration rates similar to in vivo RPTCs Schnellmann, 1995, 1996;Wills et al, 2012). RPTCs were treated for 24 hours with either vehicle control (0.5% dimethylsulfoxide), CP-809,101 (selective 5-HT 2C agonist), or SB-242,084 (selective 5-HT 2C antagonist).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RPTCs were plated in XF-96 plates and grown under improved culture conditions that maintain polarity, differentiated function, and respiration rates similar to in vivo RPTCs Schnellmann, 1995, 1996;Wills et al, 2012). RPTCs were treated for 24 hours with either vehicle control (0.5% dimethylsulfoxide), CP-809,101 (selective 5-HT 2C agonist), or SB-242,084 (selective 5-HT 2C antagonist).…”
Section: Resultsmentioning
confidence: 99%
“…Our drug discovery program in MB has previously identified several pharmacological targets that activate PGC-1a and induce MB, including the b 2 adrenergic receptor, phosphodiesterases inhibitors, and the 5-HT 2 class of receptors (Rasbach et al, 2010;Wills et al, 2012). Of these targets, the role of the 5-HT 2 receptor in mitochondrial signaling has been explored the least.…”
Section: Introductionmentioning
confidence: 99%
“…Another agonist of beta 2 -adrenoceptors, formoterol, stimulated mitochondrial biogenesis in cultured adult feline cardiomyocytes (Wills et al 2012) and rabbit renal tubule cells (Wills et al 2012, Peterson et al 2013. Interestingly, isoproterenol and NE were ineffective in these in vitro models (Wills et al 2012, Peterson et al 2013. It has been demonstrated that the betaadrenoceptor pathway enhances mitochondrial function in human neural stem cells (Chiang 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo administration of clenbuterol, a beta 2 -adrenoceptor agonist, induced prominent ultrastructural changes in mitochondria in the skeletal muscle of mice (Sundal and Sharma 2007). Another agonist of beta 2 -adrenoceptors, formoterol, stimulated mitochondrial biogenesis in cultured adult feline cardiomyocytes (Wills et al 2012) and rabbit renal tubule cells (Wills et al 2012, Peterson et al 2013. Interestingly, isoproterenol and NE were ineffective in these in vitro models (Wills et al 2012, Peterson et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation